The relationship between maternal fear of hypoglycaemia and compliance in children with insulin dependent diabetes mellitus - Freckleton, E.; Sharpe, L.; Mullan, Barbara (Springer New York LLC, 2013)
Background - Regular blood glucose monitoring is important for children with type-1 diabetes; however, the relationship between maternal fear of hypoglycaemia and glycaemic control is not well understood. Purpose-The relationship between maternal beliefs about diabetes, concerns about glycaemic control and adherence to recommended blood glucose levels in young children with type-1 diabetes were examined in this study. Method- Seventy-one mothers with children under 13 were recruited, and a prospective design was used. Demographics, maternal self-reported hypoglycaemic fear and illness perceptions were measured at baseline. Self-report daily blood sugar levels were recorded over 1 week, and glycosylated haemoglobin (HbA1c) blood glucose levels were collected at baseline and 3 months later. Results- High maternal fears of hypoglycaemia were predictive of suboptimal daily glycaemic control (elevated blood glucose levels), irrespective of illness duration or age at diagnosis. Conclusion- The results suggest that mothers who worry most about hypoglycaemia compensate by maintaining their child’s blood glucose levels above recommended levels. Elevated blood glucose levels have important consequences for long-term health, and further research could explore ways to target maternal fear of hypoglycaemia.